Avaliação da resistência à erosão a quente de revestimentos cerâmicos YSZ depositados por aspersão térmica - Góes, Wellington Uczak de (2016)
The present work has the main objective to study the behavior of YSZ (Yttria Stabilized Zirconia) deposited by thermal spraying exposed to solid particle hot erosion. The YSZ coatings, whose function is to decrease the heat transfer, are deposited over a metal coating layer of NiCrAlY (nickel, chromium, aluminum and yttrium), which has the function to protect against oxidation. The union of these layers form the coating of the type TBC (Thermal Barrier Coating), generally used for protection of gas turbine components against the action of elevated temperature and oxidizing environment. In addition to the high temperatures, these coatings can also be subjected to the impact of solid particles, that comes with the dust that pass through the filters, or that comes from the compression stages or combustion chamber and that comes from the fuel burns, leading to the wear of the coating. In order to understand the phenomenon and the implications of this for the application of coatings, it was evaluated the resistance of these coatings facing the erosive wear at high temperatures, evaluating the influence of the chemical composition, impingement angles and the temperature used. The tests were performed from 700 to 900 ºC, under different impingement angles of 30 º and 90 º. In all tests, the impact velocity, the flow and the abrasive particles were maintained constant, and the test was based in the ASTM G 76. The worn surfaces of the coatings were studied by optical profilometry and scanning electron microscopy. With the different commercial alloys, it was found that the YSZ 7Y 1,7Hf coating with lower porosity and more adherent coating obtained a higher wear resistance. The mechanism of mass loss observed was by individual rupture and detachment of the lamellae from the coating by the intersection of cracks. A reduction in the mass loss of the coatings was observed with the increasing of the temperature, within the temperatures used in the work. For the roughness of the coatings, the erosion rate was shown to be directly proportional, wherein with the decrease in erosion rate there was a reduction in the roughness of the coatings. As for the effect of the angle of impingement, it was observed that with the increase of the angle of impingement higher was the erosion rate.